Ferroelectric, piezoelectric and pyroelectric properties of sol-gel derived sodium bismuth titanate and ceramic powder-polymer composite / Nurain Ab. Halim - Nurain Ab. Halim, Ab. Halim (2018)
The dielectric, piezoelectric, pyroelectric and ferroelectric properties of sodium bismuth titanate (BNT) ceramics and its polymer composites were studied. This work is divided into three parts. In the first part, the BNT nanoceramics of molar composition 50/50 (Na0.5Bi0.5TiO3) was synthesized by a sol-gel processing method. The BNT nanoceramics were sintered at four different sintering temperatures; 900 C, 1000 C, 1100 C and 1200 C. BNT crystallized in the rhombohedra perovskites structure where Na0.5Bi0.5TiO3 was obtained from the precursor gel by heating at 700 C for 2 hours in air. The BNT nanoceramics sintered at 1100 C temperature exhibits high crystallinity, good dielectric properties (at 1 kHz,